Cognitive Dissonance and Persuasive Reasoning: A Psychological Study of Argument Construction in Essay Writing (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study is a mixed-methods empirical research that explores how cognitive dissonance shapes the argumentative writing of third-year English language learners at the University of Frères Mentouri (Constantine1, Algeria). Anchored in the theoretical frameworks of persuasive reasoning and cognitive dissonance, the research investigates whether intentional exposure to conflicting evidence enables the students to construct persuasive essays. The quantitative analysis of the persuasive essays written by sixty (60) undergraduate EFL learners disclosed significant improvements in the participants’ awareness, counterargument integration and overall reasoning capacity when instruction incorporated dissonance-based tasks. The qualitative insights that were obtained from the students' reflective journals corroborated these patterns; they revealed that the learners were, metacognitively, more engaged with their writing, managed emotional discomfort of contradicting reflections, and developed more effective reasoning strategies through complex issues. Together, these findings underscore the cognitive operations that support dissonance and improve argumentative competence. Extending beyond its data-driven contributions, the paper highlights the pedagogical value of integrating dissonance-orientated tasks in writing instruction to bring about critical literacy, intellectual flexibility, and second-order thinking in applied education contexts.